Effect of Post-silanization Heat Treatments of Silanized Feldspathic Ceramic on Adhesion to Resin Cement - Corazza, Pedro Henrique [UNESP]; Mota Cavalcanti, Samia Carolina [UNESP]; Cavalcanti Queiroz, Jose Renato; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe (Quintessence Publishing Co Inc, 2013)
Purpose: To evaluate the effect of post-silanization heat treatment of a silane agent and rinsing with hot water of silanized CAD/CAM feldspathic ceramic surfaces on the microtensile bond strength between resin cement and the ceramic, before and after mechanical cycling.Materials and Methods: Blocks measuring 10 x 5.7 x 3.25 mm(3) were produced from feldspathic ceramic cubes (VITA Mark II, VITA Zanhfabrik). Each ceramic block was duplicated in composite resin using a template made of polyvinylsiloxane impression material. Afterwards, ceramic and corresponding resin composite blocks were ultrasonically cleaned and randomly divided according to the 5 strategies used for conditioning the ceramic surface (n = 10): GHF: etching with hydrofluoric acid 10% + rinsing with water at room temperature + silanization at 20 degrees C; G20: silanization; G77: silanization + oven drying at 77 degrees C; G20r: silanization + hot water rinsing; G77r: silanization + oven drying at 77 C + hot water rinsing. The resin and ceramic blocks were cemented using a dual-curing resin cement. Every group was divided in two subgroups: aging condition (mechanical cycling, designated as a) or non-aging (designated as n). All the bonded assemblies were sectioned into microsticks for microtensile bond strength (mu TBS) testing. The failure mode of the tested specimens was assessed and mu TBS data were statistically analyzed in two ways: first 2-way ANOVA (GHF, G20 and G77 in non-aging/aging conditions) and 3-way ANOVA (temperature x rinsing x aging factors, excluding GHF), followed by Tukey's test (p = 0.05).Results: The 2-way ANOVA revealed that the mu TBS was significantly affected by the surface treatment (p < 0.001) but not by aging (p = 0.68), and Tukey's test showed that G77-n/G77-a (18.0 MPa) > GHF-n/GHF-a (12.2 MPa) > G20-n/G20-a (9.1 MPa). The 3-way ANOVA revealed that the mu TBS was significantly affected by the heat treatment and rinsing factors (p < 0.001), but not affected by aging (p = 0.36). The rinsing procedure decreased, while oven drying increased the bond strengths. Group G77, in both non-aging and aging conditions (18.6-17.4 MPa), had the highest bond values. Failure modes were mainly mixed for all groups.Conclusion: Oven drying at 77 degrees C improved the bond strength between the resin cement and feldspathic ceramic, but hot water rinsing reduced the bond strength and should not be recommended.
Keywords: adhesion; microtensile bond strength; ceramic; heat treatment; silane